Dynamic Coupling of Boltzmann Plasma Model to Surface Erosion Model for Kinetic Treatment of Plasma-Material Interactions. (2nd January 2017) - Keniley, S.; Curreli, D.
Abstract : We present an innovative coupled Boltzmann–binary collision approximation (BCA) method for the simulation of the near-wall plasma in the presence of a material-releasing wall. The method is based on a full-f multispecies Boltzmann solver for the plasma (charged and neutral species) coupled to a modification of the classical BCA code TRIDYN. Both the plasma ions and the impurities are treated as Boltzmann kinetic species, allowing high resolution even at very disparate densities, particle fluxes, drift velocities, and energy fluxes. From the distribution functions, all the fluid moments (density, heat flux, etc.) and the net and gross erosion rates are derived. An example of calculation of a helium plasma facing a beryllium wall is reported, showing the evolution of the phase-spaces of ions, neutrals, and material impurities in the near-wall region at nominal ITER conditions.